Evaluation Aspects for Ecological Risk in Operation of Field Sprayers (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Intensive agricultural production is closely linked with the application of plant protection means, as well as use of field sprayers. When intensive technologies are used, crops as are treated with pesticides several times during the vegetation period. All chemicals applied for plant protection are more or less dangerous to human health and environment. Particularly dangerous is the use of unchecked and defective field sprayers, non-observance of the stated rates of pesticides, agrotechnical treatment terms, as well as wrong adjustment of the sprayers. Standard ISO 14001 states the basic measures for establishment and maintenance of environmental management system. In the article is presented the model of environmental management system for field sprayers based on given standard. The evaluation system includes technical and organizational measures having an influence on the pollution of environment and human health. This system includes the analysis of the factors, planning, regular inspection of field sprayers, training of serving staff and the corrective measures. During the operation of field sprayers the local atmospheric, ground, and water pollution is to be observed that in its turn is conductive to the choking up of agricultural field crop and animal products. The levels of ecological risk include the accumulation of pesticides into environment, as well as ecological risk connected with the increased human morbidity and disappearance of individual species of plants and animals. Proposed environmental management system for field sprayers can serve as a basis to develop and introduce the system of periodical inspections for field sprayers. The environmental management system for field sprayers will promote more effective protection of people and environment.